2019
DOI: 10.1111/itor.12630
|View full text |Cite
|
Sign up to set email alerts
|

Logical rules characterization of online consumer trust

Abstract: In this study, we address the discriminant factors of website trust. We specifically build sets of propositional rules that can be used to predict the level of trustworthiness of a site. Focusing on initial trust, a survey was designed to assess site characteristics observed by the respondent and his/her perceptions around appearance, reputation, fulfillment, and security. By exploring data, we look for the most favorable rules classifiers among decision trees as well as classical and dominance-based rough set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…They showed that negative‐valent perceptions were more useful in predicting low levels of trust than positive‐valent perceptions in predicting high trust. In their empirical study, characteristics usually considered important, such as errors, design, and support, did not seem to influence the decision to trust, even if “they may contribute to create a certain context” (Andrade et al., 2021, p. 21).…”
Section: Background Theory and Assumptionsmentioning
confidence: 97%
See 3 more Smart Citations
“…They showed that negative‐valent perceptions were more useful in predicting low levels of trust than positive‐valent perceptions in predicting high trust. In their empirical study, characteristics usually considered important, such as errors, design, and support, did not seem to influence the decision to trust, even if “they may contribute to create a certain context” (Andrade et al., 2021, p. 21).…”
Section: Background Theory and Assumptionsmentioning
confidence: 97%
“…Andrade et al. (2021) recently proposed using rough sets and decision trees to predict levels of trust in websites. They showed that negative‐valent perceptions were more useful in predicting low levels of trust than positive‐valent perceptions in predicting high trust.…”
Section: Background Theory and Assumptionsmentioning
confidence: 99%
See 2 more Smart Citations